Establishment and applications of male germ cell and Sertoli cell lines. Issue 2 (August 2016) - Wang, Hong; Wen, Liping; Yuan, Qingqing; Sun, Min; Niu, Minghui; He, Zuping
Abstract : Within the seminiferous tubules there are two major cell types, namely male germ cells and Sertoli cells. Recent studies have demonstrated that male germ cells and Sertoli cells can have significant applications in treating male infertility and other diseases. However, primary male germ cells are hard to proliferate in vitro and the number of spermatogonial stem cells is scarce. Therefore, methods that promote the expansion of these cell populations are essential for their use from the bench to the bed side. Notably, a number of cell lines for rodent spermatogonia, spermatocytes and Sertoli cells have been developed, and significantly we have successfully established a human spermatogonial stem cell line with an unlimited proliferation potential and no tumor formation. This newly developed cell line could provide an abundant source of cells for uncovering molecular mechanisms underlying human spermatogenesis and for their utilization in the field of reproductive and regenerative medicine. In this review, we discuss the methods for establishing spermatogonial, spermatocyte and Sertoli cell lines using various kinds of approaches, including spontaneity, transgenic animals with oncogenes, simian virus 40 (SV40) large T antigen, the gene coding for a temperature-sensitive mutant of p53, telomerase reverse gene ( Tert ), and the specific promoter-based selection strategy. We further highlight the essential applications of these cell lines in basic research and translation medicine.